Compression Myelopathy Caused by Anterolisthesis and Hypertrophic Ligamentumflavum in the Adjacent Segment 11years after Cervical Laminoplasty-A Case Report and Review of the Literature - Sho Dohzono; Sadahiko Konishi; Hidetomi Terai; Hiromitsu Toyoda; Akinobu Suzuki; Hiroaki Nakamura (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2014)
Introduction: Symptomatic adjacent segment disease after anterior cervical decompression and fusion has been well described, but there have been few reports of symptomatic adjacent segment disease after cervical laminoplasty.  Case report: The authors report on a 69-year-old female gradually developed gait disturbance due to C7 anterolisthesis and ligamentumflavum thickening with an onset 11 years after conventional C3-7 laminoplasty. The patient underwent laminectomy from C6 to T1 and was able to return to ambulation. However, she experienced further deterioration in her ambulatory status four years after the second surgery, due to further anterior slippage of C7.Finally; she underwent posterior decompression and fusion from C5 to T3. The patient was able to return to ambulation with the assistance of a cane despite some level of spasticity.  Conclusion: Compression myelopathy may occur as a late effect adjacent segment disease that produces a deteriorated condition after conventional cervical laminoplasty. Anterolisthesis with thickened ligamentumflavum at the cervico-thoracic junction needs to be fused and instrumented.